The pedagogical control of students’ physical preparedness taking into account their individual anthropometrical characteristics - Баламутова [Balamutova N.], Наталія Михайлівна (Slobozhanskyi Herald of Science and Sport, 2012)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]-->Were considered the most accessible and objective methods for assessing the physical development of students, which were expressed in the construction valuation tables of individual anthropometric. Intheexperimentparticipated 1300 ofyoungstudents of 1–2 courses. The interrelation of the activity of students’ physical preparedness with peculiarity of their figure was established. Thus, the opinion of the necessity of taking into account individual anthropometrical characteristics during the composition control standards was confirmed. Developed method of the appraisal of students’ physical preparedness which takes into account their individual anthropometrical characteristics may be used for building lists of physical standards in different high educational establishments and students.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->